Factors of Interest in Becoming a Teacher among Beauty Education Study Program Students - Nur Shabrina; Sri Endah Wahyuningsih (Jurnal Penelitian Pendidikan, 2024)
Study This aiming For know What just factor interest Beauty Education study program students to teacher profession . Factors studied in study This is a perception factor , an ability factor self , value and desire factors , opportunity factors work , environmental factors , and experience factors . Including in study quantitative with method research used is analysis statistics descriptive and factor analysis . It is type study survey and measurement instrument with scale likert . Application assisted data processing with Microsoft Excel and IBM SPSS Statistics 23. Research results show that in a way factor analysis of the six factors each other reliable and forms two major factors namely the intrinsic factors that consist from the perception factor with statistical average result descriptive by 84.2%, capability factor self 81.6%, and experience factor 78%. Second factor namely extrinsic factors consisting of from the value and desire factors with statistical average descriptive by 67.7%, opportunity factor work 63.9%, and environmental factors 58.1%.